Design, Synthesis and Biological Activity of Low‐Molecular‐Weight URAT1 Inhibitors. Issue 5 (1st February 2023) - Chen, Siliang; Chen, Ya; Yang, Zhongcheng; Huang, Wanqiu; Cao, Zhijun; Wang, Xuekun; Yao, Huixin; Li, Zheng; Wang, Guangji
Abstract: Hyperuricemia has become a global problem and is one of the four basic metabolic diseases after hypertension, hyperlipidemia, and hyperglycemia. However, the existing drugs have undesired or serious adverse effects, such as the high risk of Stevens‐Johnson syndrome for allopurinol, and the cardiovascular side effects induced by febuxostat. Therefore, it is an urgent need to develop an effective and safety agent for the treatment of hyperuricemia. The urate transporter 1 (URAT1) inhibitors have been considered as a promising uric acid‐lowering agents. To improve adverse reactions caused by excessive lipophilicity and large molecular weight of existing drugs, five novel low‐molecular‐ weight URAT1 Inhibitors were designed and synthesized by molecular hybridisation. Among them, although compound 4 showed less potent activity than the classic URAT1 inhibitor benzbromarone in vitro, compound 4 exhibited better uric acid‐lowering activity than benzbromarone in vivo, which may be related to the fact that compound 4 has lower lipophilicity than benzbromarone to facilitate drug absorption. In addition, compound 4 cherishes some merits, which have a smaller molecular weight and lower lipophilicity, and superior in vitro activity than lesinurad. Generally, the results indicate that compound 4, with a good therapeutic effect, is a prospective candidate for the treatment of hyperuricemia. Abstract : We designed and synthesized five small molecular compounds to decrease the lipophilicity and molecular weight by molecular hybridization and scaffold hopping strategy. After comprehensive structure‐activity relationship study, the optimal compound 4 (IC50 =10.5 μM, logP=1.72) was identified as a novel URAT1 inhibitor with lower lipophilicity and low molecular weight compared to benzbromarone and lesinurad. Moreover, compound 4 exhibited significantly uric acid‐lowering effects and showed a slightly better uric acid‐lowering effect than benzbromarone in vivo .